Qualification profiles in nursing - the current situation in German speaking countries - Daxberger, Sabine [Verfasser]; Peters, Miriam [Verfasser]; Hauck, Claudia [Verfasser] (My University, 2020)
"The increasing complexity of nursing care arrangements and the current reform to the Nursing Professions Act in Germany form a context which gives rise to the question: what should be the “right” mix of qualifications in the nursing and social care sectors. Austria and Switzerland implemented reforms in nursing training several years ago. The International Council of Nurses (ICN) also proposes a graduated qualification system. This article presents skill sets in terms of formal qualifications in German speaking countries that are linked with defined task profiles. It concludes by highlighting commonalities and differences." (authors' abstract; BIBB-Doku)
Keywords: S 6.4.5 Gesundheits-, Sozial- und Erziehungsberufe; I 2.2.1 Westeuropa; Pflegeberuf; Berufsausbildung; Tätigkeitsmerkmal; Qualifikationsprofil; Nationaler Qualifikationsrahmen; Schweiz; Österreich; Bundesrepublik Deutschland